To solve the system of equations, we can use the method of substitution.
First, let's solve the second equation for x:
2x - 4y = -16
2x = 4y - 16
x = 2y - 8
Now, we substitute this expression for x into the first equation:
2(2y - 8) + 8y = 8
4y - 16 + 8y = 8
12y - 16 = 8
12y = 24
y = 2
Substituting this value of y back into the expression for x:
x = 2(2) - 8
x = 4 - 8
x = -4
Therefore, the solution to the system of equations is x = -4 and y = 2.
Solve the system of equations. 2x+8y=8 2x−4y=−16
1 answer